When and Where I Enter: Teaching the Concepts of Critical Pedagogy and Applied Sociology Through Study Abroad Programs - Karen Young; Martha Hughes (Journal of Public and Professional Sociology)
Participation of students in study abroad programs which focus on teaching the core concepts and principles in a different country enhances a student's understanding and appreciation of the host country's culture and brings alive the concept of globalization in a way that no other classroom experience in America could ever do. The University System of Georgia's European Council study abroad programs have for years offered in-depth immersion programs which have proven to be exciting, effective and reliable models for increasing a student's awareness and actively stimulating their capacity for higher learning, often leading to an increase in participatory community activism and civic engagement upon the student's return to their home campuses and community environments. When a professor has the ability to use creative teaching techniques which use examples from the experiential component gained from study and travel in a country other than a student's home country, teaching and learning come together in an exciting way in the classroom and every fact imparted to students produces a series of teaching moments whereby teaching and learning are both enhanced and intensified. As a student is guided through the learning process to look introspectively and critically at the races and cultures of our world and at the intergroup relations that emerge from ethnic, religious, cultural, class, gender and other differences, this teacher's roadmap for student learning is considered basic to developing a critical and necessary understanding of our society.